Intrafamilial phenotypic heterogeneity of epidermolytic ichthyosis associated with a new missense mutation in keratin 10. (1st April 2016) - Abdul‐Wahab, A.; Takeichi, T.; Liu, L.; Stephens, C.; Akiyama, M.; McGrath, J. A.
Summary: Mutations in the keratin 10 gene ( KRT10 ) have been shown to underlie several forms of epidermolytic ichthyosis (EI), including generalized, annular and naevoid variants. We investigated an autosomal dominant pedigree with ichthyosis in which there was intrafamilial clinical heterogeneity, with the affected individual family members presenting with features of either erythrokeratoderma progressiva, annular EI, localized or superficial EI, or more generalized EI. Sanger sequencing identified a new heterozygous missense mutation (c.457C>A; p.Leu153Met) in KRT10 in all affected individuals. No additional mutations were identified in the genes for keratin 1 ( KRT1 ) keratin 2 ( KRT2 ), connexin 31 ( GJB3 ) or connexin 30.3 ( GJB4 ) that might account for the clinical heterogeneity seen in this family. Our findings illustrate the intrafamilial variability in phenotype and diverse clinical presentations that can occur in EI resulting from a single mutation in KRT10 .